Education in the Al-Faruqi’s Perspective and Its Implementation in the Context of the Islamization of Knowledge - Ahmad Nabil Amir; Tasnim Abdul Rahman (Southeast Asian Journal of Islamic Education, 2022)
The paper analyzed Ismail Raji al-Faruqi’s (1921-1986) ideas on Islamic education and its significant impact on the Islamic world. It set forth to discusses the ideas of Islamization of knowledge (IOK) as envisaged by al-Faruqi through his works such as Islamization of Knowledge: General Principles and Work Plan, and Al-Tawhid: Its Implications for Thought and Life, which has contributed to a momentous breakthrough in Muslim education through its progressive and inclusive outlook and consciousness and vision of tawhid. The study was conducted based on library research. It qualitatively documented material and sources from significant works of al-Faruqi in archives, journals, magazines, books, transcripts, and other related materials. The data were analyzed using descriptive, analytical, and comparative methods. The study concluded that al-Faruqi has brought forth a universal Islamic worldview that propounded a transcendental religious and philosophical outlook based on his rational and universal ideal and standpoint. His philosophical ideal was founded on the critical methodology of tawhid that was instrumental in projecting his Islamization of knowledge project and propounding its scientific and rational outlook that aspires to revive the spirit of reform and reconstruct ijtihad and reclaim the creative and universal religious spirit and moral dynamics of the ummah. Al-Faruqi's contribution to the advancement of Islamic Education includes outlining the systemic and comprehensive principles and framework of the Islamization of Knowledge in education, social sciences, and the English language.